Composing and arranging : standard 4 benchmarks - Rinehart, Carroll A.; MENC, the National Association for Music Education (U.S.); MENC Committee on Performance Standards (Reston, VA : MENC, the National Association for Music Education, 2002)
"Now the standards and assessment process has reached its final state - identifying examples of student responses at the basic, proficient, and advanced levels for each of the standards. To accomplish this, MENCE embarked on the Benchmark Student Performances in Music project - a project to assemble benchmark student responses to the assessment strategies described in Performance Standards for Music. This current publication, the first in the Benchmarks project, focuses on the benchmark student performances in music for Standard 4. It offers examples of fourth-, eighth-, twelfth-graders' responses to strategies designed to assess progress toward the achievement standards included within Content Standard 4: Composing and arranging music with in specified guideline"-p.vii.
Provides sample musical responses by students in grades K-12 to assessment strategies described in the MENC publication Performance standards for music (c1996).
Includes bibliographical references (p. 193-196).
Includes guidelines for using copyrighted music.
Keywords: Composition (Music) -- Instruction and study -- Evaluation; Arrangement (Music) -- Instruction and study -- Evaluation